Challenging the Uniqueness of Being by Cognizing - Pogossian, Edward M. (Mathematical Problems of Computer Science, 2021)
Humans become powered enough to question the further types of their being while there are no ways to resolve the mystery of being of cellular realities (cellulars) predetermined by a type of programs, genomes, and their universal processors. Acknowledging that genomic reproduction can not be originated by a chance, the kernel of effective cognition is universal for being in the universe and mental models can be reduced to basic classifiers, in what follows, we continue to challenge the uniqueness of human cognizing arguing possibility of origination of basic classifiers in frame of fundamentals of physicists followed by constructive formation of mental systems composed from those basic classifiers